Distribution of Rosaceae Plants in Burial Sites of Infected Host Plants and Determination of Black Shoot Blight Susceptibility by Artificial Inoculation - Mi-Hyun Lee; Jongduk Jung; Kyongnim Kim; Hyo-Won Choi; Yong Hwan Lee (Research in Plant Disease)
Erwinia pyrifoliae is a necrotrophic pathogen that causes black shoot blight in Asian (Nashi) pears. Black shoot blight was first observed in pear trees in Korea in 1995. E. pyrifoliae has only been detected in apple, and pear trees in Korea and strawberries in the Netherlands. E. amylovora, a pathogen related to E. pyrifoliae, is known to cause diseases of Rosaceae plants, but the susceptibility to black shoot blight have not been examined. Planted or naturally growing Rosaceae plants were investigated in 31 sites where black shoot blight occurred in the past from the central region of Korea. As a result, 47 kinds of plants included in 20 genera were observed. Among them, there are 38 woody plants and nine herbaceous plants. The susceptibility to black shoot blight was examined with 14 species in seven genera of the Rosaceae plants by artificial inoculation. After 5 days, the symptoms were observed at the inoculated site and were re-isolated bacteria from lesions of inoculated plants and confirmed by observing morphological characteristics on King's Medium B's medium. The bacterial isolates were further identified using real-time polymerase chain reaction using a HelixDtect EAEP detection kit. A total of 12 species of Rosaceae plants showed disease symptoms of black shoot blight, and fire blight has been shown to cause disease symptoms in a total of 11 species of Rosaceae plants. In this study, host plants of Rosaceae plants for black shoot blight were investigated, and these results can be used to monitor the occurrence of black shoot blight.